Pain and activity limitations in women and men with contemporary treated early RA compared to 10 years ago: the Swedish TIRA project. (July 2015) - Ahlstrand, I; Thyberg, I; Falkmer, T; Dahlström, Ö; Björk, M
<x xml:space="preserve">Abstract</x> Objectives: To study differences regarding pain and activity limitations during the 3 years following diagnosis in women and men with contemporary treated early RA compared with their counterparts who were diagnosed 10 years earlier. Method: This study was based on patients recruited to the Early Intervention in RA (TIRA) project. In the first cohort (TIRA-1) 320 patients were included in time for diagnosis during 1996–1998 and 463 patients were included in the second cohort (TIRA-2) during 2006–2009. Disease activity, pain intensity (Visual Analogue Scale, VAS), bodily pain (BP) in the 36-item Short Form Health Survey (SF-36), activity limitations (Health Assessment Questionnaire, HAQ), and medication were reported at inclusion and at follow-up after 1, 2, and 3 years. Results: Disease activity, pain, and activity limitations were pronounced at inclusion across both genders and in both cohorts, with some improvement observed during the first year after diagnosis. Disease activity did not differ between cohorts at inclusion but was significantly lower at the follow-ups in the TIRA-2 cohort, in which the patients were prescribed traditional disease-modifying anti-rheumatic drugs (DMARDs) and biological agents more frequently. In TIRA-2, patients reported significantly lower pain and activity limitations at all follow-ups, with men reporting lower pain than women. Women reported significantly higher activity limitations at all time points in TIRA-2. Conclusions: Pain and activity limitations were still pronounced in the contemporary treated early RA cohort compared with their counterparts diagnosed 10 years earlier and both of these factors need to be addressed in clinical settings.